Training and Assistance in the Preparation of Financial Reports for Village Enterprises in Rowotamtu Village Using Microsoft Excel: Pelatihan Dan Pendampingan Penyusunan Laporan Keuangan Badan Usaha Milik Desa Di Desa Rowotamtu Dengan Menggunakan Aplikasi Excel - Dafillah Vike Eryana; Dwi Fera Istiqomah; Siti Aisyah; Olivia Anandyta; Nurgapita Puspaningrum; Arisona Ahmad (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Makmur Sejahtera Enterprises in Rowotamtu Village, Rambipuji Subdistrict, Jember Regency, is one of the initiatives aimed at empowering the village economy through the utilization of Village Funds. However, the continued use of manual financial management has become a major obstacle to achieving transparent and accountable governance. This training and mentoring program was created to improve the skills of BUMDes managers in generating digital financial reports with Microsoft Excel. A participatory and practical approach was employed, involving stages of problem identification, hands-on practice, and evaluation. The results showed that the use of Excel significantly improved the accuracy, efficiency, and organization of financial records. Additionally, participants demonstrated an increased understanding of regulations and reporting systems. This activity proves that simple digitalization can serve as a practical solution to support transparency in village financial management. Long-term success, however, depends on the commitment and consistency of the managers in sustainably implementing the system.